Epidemiology of Epstein-Barr virus infection in pre-adolescent children: application of a new salivary method in Edinburgh, Scotland. Issue 2 (February 1998) - Crowcroft, N S; Vyse, A; Brown, D W; Strachan, D P
Abstract : STUDY OBJECTIVE: To describe the epidemiology of Epstein-Barr virus (EBV) among primary school children by testing saliva with a new EBV capsid antigen "G" antibody capture radioimmunoassay (GACRIA). DESIGN: A population based sample of 7 year old schoolchildren were followed up at age 11. SETTING: 30 randomly chosen primary schools in Edinburgh, Scotland. PARTICIPANTS: 552 schoolchildren. MEASUREMENTS: Data on risk factors for infection were collected by questionnaire at ages 7 and 11. Saliva samples collected at age 11 were examined by GACRIA for evidence of previous infection with EBV. For 102 subjects, a second salivary specimen collected approximately one month after the first sample was available for testing as a measure of the repeatability of the method. MAIN RESULTS: Unequivocal results were found in 91% of samples and the repeatability of the test was good (kappa = 0.71). Fifty six per cent of children had antibodies to EBV. In a logistic regression analysis, independent risk factors for infection were sharing a room (odds ratio 1.78, 1.14, 2.79), head of household's social class IV/V compared with I (odds ratio 2.87, 1.08, 7.34), and schools serving predominantly rented housing estates (odds ratio 2.3, 1.09, 4.84). CONCLUSION: This study is the first application of EBV viral capsid GACRIA to salivary samples. The method was successfully used to describe the epidemiology of EBV. In this study, characteristics of the home seemed to be more important than those of the school in determining the likelihood of infection with EBV.